EMISI CO2 PADA KEBUN KELAPA SAWIT DI LAHAN GAMBUT: EVALUASI FLUKS CO2 DI DAERAH RIZOSFER DAN NON RIZOSFER - Etik Puji Handayani; Komarudin Idris; Supiandi Sabiham; Sri Juniwati; Meine van Noordwijk (Jurnal Ilmu Tanah dan Lingkungan, 2019)
Sources of CO2 from the soil include root respiration, decomposition of newly fallen aboveground litter and decomposition of old soil organic matter. Rhizosphere processes play a key role in soil respiration which is the main carbon efflux from peatland ecosystem to atmosphere. Plant rhizodeposits supply low-molecular weight carbon substrates to the soil microbial community, resulting in elevated levels of activity surrounding the root. We studied the effects of rhizosphere in oil palm plantation on the fluxes of CO2. Carbon dioxide emission flux of peatland was collected in Meulaboh, West Aceh using cylindrical chambers and analysis air samples of chamber by gas chromatograph. Five-point transects perpendicular to drainage canal provided variation in depth of water  table for the samples. The data confirmed that The CO2 flux from rhizosphere chamber with additional roots was one to four times higher than from bulk soil chamber.